A New Effective And Reliable Technique For Bleeding Control İn The Modified Stoppa Approach To Acetabulum Quadrilateral Region Fractures; Ligate The Obturator Artery - Necati Doğan (Acta Medica Alanya)
Aim: This study aims to share the methods of managing foci that cause bleeding in the modified Stoppa approach to acetabulum quadrilateral region fractures. In addition, it is to reveal the amount of perioperative bleeding and the clinical effect of ligated arteries in patients whose surgery was performed with advanced bleeding control technique.Patients and methods: Between May 1, 2020, and June 30, 2023, perioperative bleeding data of 13 patients with acetabulum quadrilateral region fractures operated on with a modified Stoppa approach and advanced bleeding control technique were evaluated retrospectively. Age, gender, fracture mechanism, fracture side, fracture type, amount of perioperative bleeding, and follow-up periods were determined. The clinical effect of ligated arteries was observed in the postoperative period. In the CT scans taken in the postoperative period, the diameters of the gluteal muscles and adductor muscles were compared to the healthy side.Results: Of the 13 patients included in the study, 5 were women, and 8 were men. While the average age was 35.6 years, the average follow-up period was 15.3 months. The average number of sponges used during the modified Stoppa approach and the amount of bleeding measured with an aspirator was 284.2 ml. The middle area of the gluteal muscles compared to the healthy side was 0.89, while the average area of the adductor muscles was 0.89. No problems related to the ligated vessels were observed in any patient during the postoperative period and outpatient follow-up.Conclusions: Routine ligation of the obturator artery does not have any clinically observable adverse effects, and with advanced bleeding control, it facilitates both the hemodynamic management of the patient in terms of anesthesia and the management of the surgical field for the surgeon.